Loan Recovery Practices and Loan Portfolio Performance of Commercial Banks in Uganda: A Case of Stanbic Bank Mbale Branch - Peace Namaganda (Uganda Christian University, 2024)
This study sought to investigate the effect of loan recovery practices and loan portfolio performance of commercial banks in Uganda; a case of Stanbic bank, Mbale branch. The study objectives were; to examine the relationship between Reminder strategies and loan portfolio performance of Stanbic Bank in Mbale branch; to assess the relationship between legal and procedural enforcement and loan portfolio performance of Stanbic Bank in Mbale branch on organizational performance on organization’s reliability in Mbale city Council and To evaluate the relationship between loan monitoring and loan portfolio performance of Stanbic Bank in Mbale branch. The study population was 45 respondents with the sample size of 36 (banking officers (8), branch managers (2), loans officers (12), credit administrators (6), and customer service (4), and management trainees (10). The research sampled 36 respondents. ) selected using Krejcie and Morgan (1970) table of sample size determination, from the Stanbic bank, Mbale branch. The study employed stratified random sampling techniques in coming up with a sample size of 36 respondents. The primary data collection methods used was a questionnaire. The collected data was analyzed using descriptive statistics in SPSS version 20. Linear and Multiple regression analysis were also used to determine the effect of the independent variables on dependent variables. The study found that Reminder strategies was significant in Loan portfolio of commercial banks with R square value = 0.637(63.7%) and β =. with p-value = 0.003<0.05. The regression coefficient of Reminder strategies was positive and significant in Loan portfolio of commercial banks. Further the study found that legal and procedural enforcement had R square value = 0.972 and β = .989 with a p-value = 0.000<0.05. The regression coefficient of Loan portfolio of commercial banks was positive and significant in legal and procedural enforcement. The study further found that loan monitoring had significant effect in predicting Loan portfolio of commercial banks had R square value = 0.968 and β = .984 with a p-value = 0.000<0.05 with p-values of 0.000 less. There is a need for Stanbic Mbale branch to closely watch the reminder strategies they use to remind customers over the loan overdue because it was reported consistently that some were not user friendly to customers and others were new to the customers like interactive voice response and dunning letters this will help to increase Loan Portfolio Performance. The researcher recommends that Stanbic Mbale branch should sensitize customers on legal implication associated in case they fail to return back the loan.
Undergraduate Research